(untitled) - Vogel, Ezra F. (Cambridge, Mass., 1991)
Japan and the four little dragons--Taiwan, South Korea, Hong Kong, and Singapore--constitute less than 1 percent of the world's land mass and less than 4 percent of the world's population. Yet in the last four decades they have become, with Europe and North America, one of the three great pillars of the modern industrial world order. How did they achieve such a rapid industrial transformation? Why did the four little dragons, dots on the East Asian periphery, gain such Promethean energy at this particular time in history? Ezra F. Vogel, one of the most widely read scholars on Asian affairs, provides a comprehensive explanation of East Asia's industrial breakthrough. While others have attributed this success to tradition or to national economic policy, Vogel's penetrating analysis illuminates how cultural background interacted with politics, strategy, and situational factors to ignite the greatest burst of sustained economic growth the world has yet seen.
Keywords: Industrialization,Công nghiệp hóa; East Asia,Đông Á